PEMANFAATAN PODCAST PADA YOUTUBE SEBAGAI TRANSFORMASI DAKWAH DI ERA DIGITAL - Elce Purwandari; Depi Putri; Adi Saputra (Program Studi Manajemen Dakwah Fakultas Dakwah dan Komunikasi Islam Institut Agama Islam (IAI) Al-Azhaar Lubuklinggau, 2026)
This study aims to examine the utilization of podcasts on the YouTube platform as a form of da’wah transformation in the digital era. The focus of the study includes the role of podcasts in expanding the reach of da’wah, message delivery strategies, audience impact, and challenges in digital da’wah practices. The research method employed is a literature review, analyzing scholarly journals, books, and academic publications related to digital da’wah and podcast-based religious communication. A descriptive-analytical approach is used to identify trends and key findings from previous studies. The findings indicate that YouTube podcasts contribute significantly to enhancing the accessibility and reach of da’wah, particularly among younger generations who are closely engaged with digital technology. Various podcast formats, such as sermons, discussions, and interactive interviews, encourage innovation in conveying religious messages in a more contextual and engaging manner. Podcast-based da’wah content also has a positive impact on religious understanding, the strengthening of religious identity, and the development of constructive social behavior. However, challenges such as content competition, production quality, and the potential spread of misinformation remain critical concerns. Therefore, future research is recommended to conduct empirical studies on the effectiveness of da’wah podcasts and to further explore ethical and digital literacy aspects in managing digital da’wah content.